Cardiovascular Critical Care. Issue 9 (September 2015) - Hill, Terence; Means, Gregory; van Diepen, Sean; Paul, Timir; Katz, Jason N.
<x xml:space="preserve">Abstract</x> Objective: Acute and chronic cardiovascular comorbidities are common among critically ill individuals. It is unclear if current critical care fellowship trainees feel adequately prepared to manage these conditions. Design: Prospective, cross-sectional survey. Patients or Subjects: Trainees enrolled in U.S. critical care training programs. Setting: Accredited pulmonary/critical care, surgery/critical care, anesthesiology/critical care, and stand-alone critical care training programs. Interventions: None. Measurements and Main Results: A 19-item survey assessing trainee confidence in the management of cardiac critical illness and the performance of cardiac-specific critical care interventions was constructed using Accreditation Council for Graduate Medical Education recommendations as a reference. After validation, the survey was electronically sent to all training programs for dissemination to their trainees. Confidence scores were measured on a Likert scale from 1 to 5. A total of 134 completed surveys were analyzed. Overall, respondents reported lower confidence in managing cardiovascular compared with noncardiovascular diseases in the ICU (4.0 vs 4.6 out of 5). Likewise, they reported lower perceived competence in performing cardiovascular procedures specific to the ICU (2.9 vs 4.5 out of 5). The majority (88%) of those surveyed felt that they would benefit from increased didactic and clinical experience in the management of cardiovascular critical illness. Conclusions: Current critical care fellows may be unprepared to deal with the increasing prevalence of cardiovascular illness in the ICU. This potential educational gap warrants timely attention to ensure that future graduates have the requisite skills necessary to manage these critically ill patients and presents a unique opportunity to develop multidisciplinary partnerships for enhancing training.